The role of morphometric indicators of relief in the assessment of ecogeomorphological conditions in the Fuzuli administrative region - Abushova, Samira (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
In the assessment of ecogeomorphological conditions, morphometric indicators of relief (such as slope, elevation differences, horizontal and vertical fragmentation, exposure etc.) make it possible to determine the intensity of natural processes and the characteristics of ecological risk formation within the area. The article analyzes the morphometric indicators and ecogeomorphological assessment of the relief of the Fuzuli administrative region. The characteristics of the morphometric parameters of the relief include quantitative indicators of the degree of complexity of the formation of the relief of the earth’s surface. Morphometric indicators wich determine the complexity coefficient of the earth’s surface relief play an important role in the implementation of engineering works, as well as territorial planning. Quantities of morphometric indicators were calculated based on the digital elevation model of the relief (Aster DEM) of Azerbaijan and interpolated in the Arcmap 10.8 software to determine the degree of tension of the territory. According to the ecogeomorphological tension, the study area was divided into 3 zones and the morphometric values of each zone were given. It was determined that 36.98% of the Fuzuli administrative region has favorable conditions for the construction of infrastructure. The aim of this study. To determine the degree of ecogeomorphological tension of the area based on the morphometric indicators of the relief. This allows for identifying areas with high susceptibility to natural processes and assessing potential ecological risks. Research Methodology. The research maps, created using the Mercator projection system, have been georeferenced and aligned with the WGS 1984 UTM Zone 38N coordinate system. Based on the digital model of the relief, the morphometric indicators of the relief (horizontal and vertical fragmentation, slope, exposure) were analyzed, quantified, and the degree of ecogeomorphological tension was determined using the interpolation method in the ArcMap program. Results. The study area consists of 501.13 km² of low-voltage, 696.66 km² of medium-voltage, and 157.36 km² of high-voltage areas, which are mainly suitable for land use. Only 11.61 percent of the area has high voltage, which allows these areas to be used as pastures, as well as for tourism purposes. It is possible to carry out various tourism and recreational activities in these areas, including hiking, mountaineering, and other outdoor pursuits, taking advantage of the natural landscape and scenic relief features.